Evaluación a la gestión del departamento de talento humano y su incidencia en el desempeño laboral del personal administrativo en la Corporación Dole, año 2013 - Morejón Pazmiño, Shofre Manuel (2015)
This research was conducted at Dole Corporation, located in Babahoyo canton, Los Rios province, specifically in the Human Resource Department. The investigative process lasted 90 days from approval of the project. A diagnosis of the processes of the Department of Human Talent Dole Corporation by observation was made and expressed in flowcharts processes. The diagnosis made to the processes of the Department of Human Talent Dole Corporation allowed noting ways of implementing each step continues to incorporate new staff or rise within the corporation are scheduled in such properly and according to the characteristics of the type of company. Job performance was analyzed using surveys to determine the level of staff satisfaction highlighting that suggest training, most work in teams because they believe that improved job performance, the dying agrees that motivates the company if, among the types of motivation is the main financial and also that managers care about knowing the degree of satisfaction, and this concern to obtain pleasant work environment is derived. Managing the Human Resource Department of Dole Corporation during the period 2013 indicators was established by demonstrating that an appropriate balance of indicators is carried, so that the management in the area is on track. A report of the evaluation was made to the Department of Human Resource in which consists the main objectives that should foster a culture of compliance goals in productive projects through employees also establish an early stage of information on the method that helps to overcome personal strengths and provide clarity on logic, involving all members of the organization